2017
DOI: 10.1093/ecco-jcc/jjx120
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab Levels in Breast Milk of Nursing Mothers With Inflammatory Bowel Disease

Abstract: Vedolizumab can be detected in the breast milk of nursing mothers. Although more data are imperative, the concentrations of vedolizumab in breast milk are minute and are therefore unlikely to result in systemic or gastro-intestinal immune-suppression of the infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Vedolizumab concentrations were measured in trough blood samples obtained serially before each infusion. Vedolizumab levels were measured in St.Etienne by a commercially available ELISA (TheraDiag, France) and in Sheba by a previously described in‐house ELISA assay . Briefly, integrin alfa4‐beta7 (2 μg/mL, R&D, MN, USA) was added to pre‐plated anti‐His‐tag (4 μg/mL, R&D, MN, USA) wells of ELISA plates (Nunc, Roskilde, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Vedolizumab concentrations were measured in trough blood samples obtained serially before each infusion. Vedolizumab levels were measured in St.Etienne by a commercially available ELISA (TheraDiag, France) and in Sheba by a previously described in‐house ELISA assay . Briefly, integrin alfa4‐beta7 (2 μg/mL, R&D, MN, USA) was added to pre‐plated anti‐His‐tag (4 μg/mL, R&D, MN, USA) wells of ELISA plates (Nunc, Roskilde, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…Available information indicates that maternal VDZ use appears to produce low levels in breastmilk. 45 47 Because VDZ is a large protein molecule (molecular weight of about 147,000), absorption is unlikely, since it is probably destroyed in the infant’s gastrointestinal tract. 6 , 48 The most recent guideline of the British Society of Gastroenterology stated that while low levels of infliximab, adalimumab, certolizumab, natalizumab, and ustekinumab can be detected in breastmilk from mothers receiving these biologics, breastfed infants of mothers receiving biologics, immunosuppressants, or combination therapy have similar risks of infection and similar milestone achievement at 12 months compared with non-breastfed infants or infants unexposed to these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the concentrations of biological agents found in milk are minimal (< 1% of serum concentration) as the drug is degraded in the stomach of the child and no harm from breastfeeding on biologic therapies has been described [120]. Data for anti-interleukin 12-23 and anti-integrin are very limited but due to limited transfer detectable and their monoclonal antibody molecular structures it is presumed that they are compatible with lactation [121,122]. Women on tofacitinib are advised not to breastfeed due to the lack of data on this molecule during the lactation period.…”
Section: Postpartummentioning
confidence: 99%